2014
DOI: 10.1016/j.ab.2014.03.014
|View full text |Cite
|
Sign up to set email alerts
|

A new liquid chromatography/tandem mass spectrometry method for quantification of gangliosides in human plasma

Abstract: Gangliosides are a family of glycosphingolipids characterized by mono- or polysialic acid-containing oligosaccharides linked through 1,3- and 1,4-β glycosidic bonds with subtle differences in structure that are abundantly present in the central nervous systems of many living organisms. Their cellular surface expression and physiological malfunction are believed to be pathologically implicated in considerable neurological disorders, including Alzheimer and Parkinson diseases. Recently, studies have tentatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 39 publications
(21 reference statements)
1
41
0
Order By: Relevance
“…Kundu et al ( 15 ) observed 25 GSLs consisting of 15 acidic gangliosides and 10 neutral GSLs in human plasma by TLC separation and gas-liquid chromatography analysis. Recent advances in MS analysis allowed quantitation of the intact forms of targeted GSLs using the multiple reaction monitoring mode (16)(17)(18). However, efforts to clarify the comprehensive GSL-glycomics of human serum have been limited since the characterization of serum GSLs using TLC and MS.…”
Section: Acid Hydrolysis and Sequential Exoglycosidase Digestionmentioning
confidence: 99%
“…Kundu et al ( 15 ) observed 25 GSLs consisting of 15 acidic gangliosides and 10 neutral GSLs in human plasma by TLC separation and gas-liquid chromatography analysis. Recent advances in MS analysis allowed quantitation of the intact forms of targeted GSLs using the multiple reaction monitoring mode (16)(17)(18). However, efforts to clarify the comprehensive GSL-glycomics of human serum have been limited since the characterization of serum GSLs using TLC and MS.…”
Section: Acid Hydrolysis and Sequential Exoglycosidase Digestionmentioning
confidence: 99%
“…The third quadrupole is set to allow sialic acid to pass and to collect fragments. Triple quadrupole MS with MRM has been recently used due to the high specificity for simultaneous detection of multiple components in complex samples (Zhang et al, 2012;Lee et al, 2013;Giuffrida et al, 2014;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, other authors reported a suppression of GG precursor ion signal to ‫ف‬ 14% of the original intensity by addition of dioleoylphosphatidylcholine in the analyte ( 35 ). This result was corroborated by Huang et al ( 36 ) who also showed important suppression of the GG signals (from 22% to 51% extinction for GM2, GM3, GD2, and GD3) due to contaminants present in the extracts prepared by simple protein precipitation procedure by comparing MS signals of spiked GG standards in analyte-free extracts and in pure solvents. To avoid any potential suppression, we preferred a sample extraction aiming at depleting phospholipids and enriching the extract with GGs.…”
Section: Discussionmentioning
confidence: 55%
“…Most of the studies published in the literature do not actually use any internal standard (44)(45)(46). Some have used GM3d3 for various GG classes (GM3, GM2, GD3, and GD2) in human plasma ( 36 ) or GM1d3 for GM2 in cells and plasma ( 47 ), while others have used phospholipids ( 30,31 ). Recently, authors reported the synthesis of GG-bearing nonnatural FAs for the major classes of mammalian brain and also some tumorassociated classes, which will be valuable tools to use as internal standards for MS analyses ( 48 ).…”
mentioning
confidence: 99%